2014
DOI: 10.1186/cc13887
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation biomarkers and delirium in critically ill patients

Abstract: IntroductionDelirium is a common occurrence in critically ill patients and is associated with an increase in morbidity and mortality. Septic patients with delirium may differ from a general critically ill population. The aim of this investigation was to study the relationship between systemic inflammation and the development of delirium in septic and non-septic critically ill patients.MethodsWe performed a prospective cohort study in a 20-bed mixed intensive care unit (ICU) including 78 (delirium = 31; non-del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 46 publications
(62 reference statements)
3
61
0
2
Order By: Relevance
“…No significant relationship was found between IL‐6 and delirium in serum or in CSF. Previous findings are conflicting, with some studies reporting higher serum IL‐6 levels in participants with delirium and others not detecting such a difference . A recent study of older adults without dementia undergoing elective surgery found no association between serum IL‐6 levels and delirium in the postanesthesia care unit but found higher serum IL‐6 levels in individuals with delirium on Postoperative Day 2 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No significant relationship was found between IL‐6 and delirium in serum or in CSF. Previous findings are conflicting, with some studies reporting higher serum IL‐6 levels in participants with delirium and others not detecting such a difference . A recent study of older adults without dementia undergoing elective surgery found no association between serum IL‐6 levels and delirium in the postanesthesia care unit but found higher serum IL‐6 levels in individuals with delirium on Postoperative Day 2 .…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, previous studies on circulating levels of interleukin‐6 (IL‐6) in individuals with delirium are conflicting. Most studies have reported higher levels in participants with delirium, but others have not found a relationship . IL‐6 in CSF from individuals with delirium has been studied less.…”
mentioning
confidence: 99%
“…For example, inflammation has recently been shown to be an important contributor to delirium and long-term cognitive dysfunction (37)(38)(39)(40). Indeed, all ARDS patients in our cohort had severe sepsis at the time of ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…It is significant that in this model of acute systemic inflammation TNF-α alone is sufficient to induce acute dysfunction in a cognitive task reliant on attentional and working memory function, two key cognitive domains impaired in delirium. Associations between delirium and TNF-α in biomarker studies have sometimes (Adamis et al, 2011, Kazmierski et al, 2014), but not always (van den Boogaard et al, 2011, Ritter et al, 2014), been detected. The current data are certainly supportive of deleterious effects of systemic inflammation on short-term cognitive processes.…”
Section: Discussionmentioning
confidence: 99%